Building maintenance management in public school of Malaysia - Nurmalia, Mohd Fakri (2017)
An effective plan for maintenance management system is crucial as the challenges in maintaining the nation’s educational facilities has grown wider because of the aging factor of schools’ buildings in Malaysia. Moreover, the implications of negligent facilities could be the real danger. The effectiveness of school maintenance protects capital investment and significantly it ensures the health and safety of the children and supports educational performance. This research is conducted to identify the major problems of building maintenance management system within public schools in Malaysia. In the process to achieve the objectives established, this research has been organized in combination of literature review, data collection and data analysis which has been conducted using average index analysis method. Primary data collection has been carried on 6 schools which involving questionnaire distribution to 62 respondents from different positions. As the results, the findings had proven that the performance of maintenance management system in public school still minor of requirement expectation and due to improper maintenance practice, many aspects should be improved. Therefore, in the effort to establish an effective maintenance management, strategic planning has been recommended to achieve high quality and cost effectiveness as well as to optimize the maintenance performance of their school.